IMPLEMENTATION OF A THREE-LEVEL MODEL OF DOCUMENTATION ON TRANSFER PRICING ON UKRAINE - KRUGLIAK, VIACHESLAV (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article introduces the implementation of a three-tier transfer pricing documentation model in Ukraine. This model is consistent with the approach to transfer pricing documentation developed by countries that are members of the OECD/G20. Such documentation is intended to ensure that taxpayers properly: take into account the transfer pricing rules; provide tax authorities with the information necessary to conduct a reasonable assessment of transfer pricing risks; provide tax authorities with information useful for reducing the number of disputes and simplifying the resolution of disputes between tax authorities and taxpayers in the field of transfer pricing. The article explores the issues of using a significantly updated and expanded structure of transfer pricing documentation in order to ensure the implementation in Ukraine of effective tax control over taxpayers' compliance with transfer pricing rules. Determined a list of domestic regulatory legal acts developed to ensure the implementation of a three-tier transfer pricing documentation model has been . The introduction of such a three-tier model is a step towards the formation of an integral system of control over the observance of the “arm's length” principle, which should take into account not only the observance of this principle by an individual taxpayer, but also should take into account the components of tax planning of an international group of companies if such participants belong to the group, as well as provide an objective assessment of the completeness of the formation of the object of taxation of the Ukrainian company in the context activities of the group as a whole. It is concluded that, given the transition to a three-tier model of transfer pricing documentation, both the content and the amount of information that will be used in the implementation of tax control over taxpayers' compliance with transfer pricing rules will increase.
Keywords: transfer pricing; Base erosion and Profit Shifting – BEPS; tax control; transfer pricing risks; controlled transactions; monitoring of controlled transactions